Evaluation of a computer-based bilingual breastfeeding educational program on breastfeeding knowledge, self-efficacy and intent to breastfeed among rural Hispanic women. (July 2016) - Joshi, Ashish; Amadi, Chioma; Meza, Jane; Aguire, Trina; Wilhelm, Sue
Highlights: We implemented a Computer enabled bi-lingual breastfeeding educational program in pregnant rural Hispanic women. We examined the effect on breastfeeding knowledge, self-efficacy, and intention to breastfeed postpartum at days 3 and 7, weeks 2 and 6, months 3 and 6. There was improvement in knowledge, self-efficacy and intent to breastfeed among participant in the intervention group. The intervention group showed significant improvement in knowledge at week 2. The control group reported higher negative breastfeeding sentiments at day 3 and 7. Abstract: Objective: To evaluate the impact of an interactive, computer based, bi-lingual breastfeeding educational program on breastfeeding knowledge, self–efficacy and intent to breastfeed among rural Hispanic women living in Scottsbluff, Nebraska. Methods: A two-group, repeated measures quasi-experimental study was conducted to evaluate the impact of a breastfeeding intervention. Forty six rural Hispanic women between ages 18 and 38 years were enrolled at the Regional West Medical Center in Scottsbluff, Nebraska. Study participants were randomized into intervention and control groups, with the intervention group (n = 23) receiving bi-lingual (English and Spanish) breastfeeding education on a touch screen computer program, while the control group received printed educational material. Study participants were enrolled during their last six weeks of pregnancy, with follow up assessments conducted post-partum at days 3 and 7, weeks 2 and 6, and months 3 and 6. The study protocol was approved by the University of Nebraska Medical Center Institutional Review Board (IRB protocol #430-12-EP) and City University of New York Institutional Review Board (IRB protocol # 642980-1). Results: A significant improvement in the breastfeeding knowledge and intent to breastfeed scores was seen over a 6 month period among all the study participants (p < 0.05). There was a gradual increase in the breastfeeding self-efficacy scores till week 6 followed by a decrease in self-efficacy scores at month 3 (p = 0.46), and month 6 (P = 0.54). Breastfeeding knowledge scores differed significantly between the study participants in the control and intervention groups at week 6 (p = 0.03). There were no significant differences in the breastfeeding knowledge between the control and intervention groups at other time points. The control group showed gradual decline in their self-efficacy scores at month 3 and month 6 compared to the intervention group that showed a gradual increase in their self-efficacy scores at different time points during their follow up period. However, there were no significant differences in the self-efficacy scores between the intervention and control groups at different points. The control group showed significantly higher negative breastfeeding sentiment scores compared to the intervention group at days 3 (p = 0.02) and 7 (p = 0.03) indicating a lower intent to breastfeed. Conclusion: Hispanic women living in rural settings showed improvement in breastfeeding knowledge, self-efficacy and intent to breastfeed using the computer based bi-lingual educational program. Results show week 6 and month 3 to be the critical time points of intervention so that women continue to breastfeed.